2008
DOI: 10.1002/app.29346
|View full text |Cite
|
Sign up to set email alerts
|

A thermally regenerable composite sorbent of crosslinked poly(acrylic acid) and ethoxylated polyethyleneimine for water desalination by Sirotherm process

Abstract: Crosslinked poly(acrylic acid) (XPAA) made by copolymerization of acrylic acid and ethylene glycol dimethacrylate in bulk was further reacted with 80% ethoxylated polyethyleneimine, and the latter insolubilized by treatment with glutaraldehyde. The resulting composite sorbent, XPAA(EPEI.XG), containing carboxylic acid groups and weakly basic tertiary amine groups in close proximity in the same resin bead exhibited thermally regenerable desalination property, simulating the wellknown Sirotherm TM resins. For Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Recent studies [16,17] on thermally regenerable composite (Sirotherm-type) resins showed that a weak acid/weak base mixed bead resin had a substantially reduced ion adsorption capacity at higher temperatures. Heating from 30°C to 80°C reduced the capacity by a factor of 8 [16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies [16,17] on thermally regenerable composite (Sirotherm-type) resins showed that a weak acid/weak base mixed bead resin had a substantially reduced ion adsorption capacity at higher temperatures. Heating from 30°C to 80°C reduced the capacity by a factor of 8 [16].…”
Section: Introductionmentioning
confidence: 99%
“…The "Plum pudding" resin structure, which is prepared by embedding microparticles of polyamines and microparticles of polyacids in a water and salt permeable matrix, has been discussed by Bolto and Jackson [8]; who also described the disadvantage of the presence of a high proportion of inert polymeric matrix material, which tends to limit the thermally regenerable capacity of a particular resin. Studies have been carried out by Hatch [25], Bolto and Jackson [8] and Chanda et al [16] to overcome this issue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 The current technology to bind multivalent ions is based commonly on the use of ion exchange resins (IEX). 3,4 Regeneration of IEX typically involves high temperatures [5][6][7] or consecutive washing steps involving brine or acid and caustic, 8 leading to a large amount of waste salt. 9,10 The disposal of these salts cause salinization of surface waters and soil, which is an increasing burden for the environment.…”
Section: Introductionmentioning
confidence: 99%